Bifidobacterium and Lactobacillus Counts in the Gut Microbiota of Patients With Bipolar Disorder and Healthy Controls - Aizawa, Emiko; Tsuji, Hirokazu; Asahara, Takashi; Takahashi, Takuya; Teraishi, Toshiya; Yoshida, Sumiko; Koga, Norie; Hattori, Kotaro; Ota, Miho; Kunugi, Hiroshi (Frontiers in Psychiatry, 2019)
ABSTRACT Background: Although the pathophysiology of bipolar disorder remains elusive, growing evidence suggests the beneficial effects of Bifidobacterium and Lactobacillus in the gut microbiota on stress response and depressive symptoms. In the present study, we examined Bifidobacterium and Lactobacillus counts for association with bipolar disorder and serum cortisol levels. Methods: Bacterial counts in fecal samples were examined in 39 patients with bipolar disorder according to the Diagnostic and Statistical Manual of Mental Disorders, 4th edn. and 58 healthy controls using bacterial rRNA-targeted reverse transcription-quantitative polymerase chain reaction. Results: No significant difference was found in either bacterial counts between the two groups. However, we found a significantly negative correlation between Lactobacillus counts and sleep ( = -0.45, P = 0.01). Furthermore, a significant negative correlation was found between Bifidobacterium counts and cortisol levels ( = -0.39, P = 0.02) in the patients, although such a correlation was not found for Lactobacillus counts. Conclusions: Our results suggest that Bifidobacterium or Lactobacillus counts may not play a major role in the pathophysiology of bipolar disorder in our sample. However, the observed negative correlation between Lactobacillus counts and sleep and that between Bifidobacterium counts and serum cortisol levels points to the possible roles of these bacteria in sleep and stress response of the patients.